Long-term removals of organic micro-pollutants in reactive media of horizontal subsurface flow constructed wetland treating landfill leachate. (September 2020) - Witthayaphirom, Chayanid; Chiemchaisri, Chart; Chiemchaisri, Wilai; Ogata, Yuka; Ebie, Yoshitaka; Ishigaki, Tomonori
Highlights: Phenol and PAE removals in constructed wetlands with reactive media was investigated. Their removals through adsorption, biodegradation and plant uptake were quantified. The presence of iron powder in media enhanced organic micro-pollutant removals. CW with reactive media could be applied for remediation of landfill leachate. Abstract: In this work, the removals of organic micro-pollutants (OMPs), i.e. DEP, DBP, 2, 6-DTBP, BHT, and DEHP in sand, clay and iron powder mixed media of horizontal subsurface flow constructed wetland (HSSF) from landfill leachate were investigated over 3 years period. The biodegradation was mainly responsible for the removals of DEP, DBP, 2, 6-DTBP and BHT whereas DEHP was initially removed through adsorption and formation of iron-organic complex and then subsequently biodegraded during long-term operation as OMP degrading microbial consortium attached to the reactive media was enriched. This study demonstrates that an application of reactive HSSF system can be a viable option for advanced landfill leachate treatment to meet ecological safety level.